Monoesters for transformer insulating liquid - Abdul Rajab; Melda Latif; Muhammad Imran Hamid; Tesya Uldira Septiyeni (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
The development of low viscosity insulating liquids derived from natural esters is conducted in our laboratory. Nine monoesters, i.e., methyl myristate, ethyl myristate, isopropyl myristate, methyl palmitate, ethyl palmitate, isopropyl palmitate, methyl stearate, ethyl stearate, and isopropyl stearate were synthesized from alcohols and saturated fatty acids. Treatments were performed to reduce water and acid contents and improve the oxidation stability of the monoesters. Some fundamental properties, such as breakdown voltage, kinematic viscosity, density, water content, acidity, and oxidation stability, were tested before and after treatments. The results are evaluated based on the international electrotehnical commission (IEC) standard specifications for low-viscosity monoesters derived from natural esters, IEC 62770. Except for the water content, all other properties have good compliance with the standard. The treatments reduced the water content significantly, but the values are still slightly higher than that specified by the standard.